PERENCANAAN KURIKULUM PENDIDIKAN AGAMA ISLAM YANG RESPONSIF TERHADAP KEBUTUHAN DI SEKOLAH DAN MADRASAH - Nur Hasanah; Agus Pahrudin; Agus Jatmiko; Koderi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The curriculum is an idea in the implementation of education. Without the formation of a curriculum, the results of learning will be unfocused and have no definite purpose. The purpose of this study is to determine the planning of the PAI curriculum in schools and madrasas so that the curriculum is planned in accordance with the needs of educators and students. The research method used in this study is library research. The data collection technique involved exploring data through literature review, reading, examining, and recording data from various relevant sources, such as articles, journals, and books. The results of this study on the elements of PAI curriculum planning are expected to create a young generation that is not only academically intelligent but also has good character and is able to contribute positively to society.